Free-Tissue Transfer for the Reconstruction of War-Related Extremity Injuries: A Systematic Review of Current Practice. Issue 1 (1st January 2016) - Theodorakopoulou, Evgenia; Mason, Katrina A.; Pafitanis, Georgios; Ghanem, Ali M.; Myers, Simon; Iwuagwu, Fortune C.
ABSTRACT: Objectives: Extremity injuries in combat zones have devastating sequelae. The increasing survival of war-zone casualties, combined with rapid advances in microsurgery, means that there is a growing role for free-tissue reconstruction. We systematically reviewed the current practices in microsurgical reconstruction of combat-related extremity injuries, focusing on free-flap types, timing of surgery, and outcomes. Methods: We conducted a PubMed search of the terms "War" and "Reconstruction, " identifying 21st century studies on subacute/delayed free-flap repair, to reflect the idiosyncrasies of modern warfare. Case reports and studies exclusively describing craniofacial and thoracoabdominal injuries were excluded. Results: A total of 11 studies fulfilled our inclusion criteria. In 9 studies, patients were repatriated/transferred to specialist facilities for treatment; in 2 studies, reconstruction was performed within combat/austere environments. The number of free-flaps described per study ranged from 6 to 233 (Total = 501). Latissimus dorsi flaps were most commonly used (43.7%). The average time to definitive reconstruction ranged from 9.6 days to 3 years, being delayed to address life-threatening injuries. The average free-flap success rate was 95.5% (range = 88.9%–100%). Conclusion: Combat-associated extremity injuries are characterized by extensive tissue loss and gross contamination. Despite this, microsurgical reconstruction results in minimal morbidity and successful outcomes. Large, multicenter studies are necessary to corroborate these findings and establish definitive management guidelines.